Justin, Tatian and the Forging of a Christian Voice - Whitmarsh, Tim (Zeitschrift für antikes Christentum, 2024)
This article considers the construction of the speaking subject in Justin’s First Apology and Tatian’s To the Greeks , two interlocking texts (often associated with the problematic genre of Christian apologetics). Bracketing questions of biographical reality, it explores the fictionalising techniques Justin and Tatian adopt to magnify their own authority, co-opt well-known narrative models (including martyrologies and imitatio Christi ) in the service of their own self-fashioning. I take their autobiographies as stylised self-dramatisations, rather than guides to historical realities. There are strong parallels with the kind of self-modelling that we see in the works of pagan sophists of the era, notably Dio Chrysostom. Reading these two authors in this way blurs the sharp distinctions they seek to draw between Christian and pagan. It also requires a reading of their texts, in line with recent scholarship, as generically complex, sophisticated and absorbent, and open to the opportunistic appropriation of elements characteristic of pagan literature of the era. Foucault has argued that the voice of early Christianity was characterised by its confessional quality, which was new, confident and distinctive; this article argues, by contrast, that Justin and Tatian at any rate were intellectual bricoleurs and experimentalists, and had much more in common with their pagan peers.